1995
DOI: 10.3346/jkms.1995.10.6.462
|View full text |Cite
|
Sign up to set email alerts
|

Systemic lupus erythematosus with obstructive uropathy: Case report and review

Abstract: We report a case of patient with documented SLE who displayed dysuria, gastrointestinal (GI) symptoms and renal insufficiency associated with the unusual occurrence of bilateral hydroureteronephrosis due to urterovesical junction stricture (obstructive uropathy). Pathologic investigations disclosed chronic interstitial cystitis (IC) with evidence of focal immune complex deposition in the blood vessel walls of the bladder. The GI symptoms and dysuria regressed with initial therapy for SLE with steroids. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
23
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 0 publications
0
23
0
Order By: Relevance
“…13 Typical symptoms are suprapubic discomfort, dysuria, urgency, frequency, and nocturia. 6,14 The urine is sterile, ultrasound or CT scan demonstrate a markedly reduced bladder size with thickened bladder mucosa, and cystoscopy additionally may show stellate scars and ulcers. Lupus interstitial cystitis is frequently associated with an obstructive uropathy (in 17 of 21 in 1 review, 6 ) especially hydroureteronephrosis resulting from edema or fibrosis at the ureterovesical junction.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…13 Typical symptoms are suprapubic discomfort, dysuria, urgency, frequency, and nocturia. 6,14 The urine is sterile, ultrasound or CT scan demonstrate a markedly reduced bladder size with thickened bladder mucosa, and cystoscopy additionally may show stellate scars and ulcers. Lupus interstitial cystitis is frequently associated with an obstructive uropathy (in 17 of 21 in 1 review, 6 ) especially hydroureteronephrosis resulting from edema or fibrosis at the ureterovesical junction.…”
Section: Discussionmentioning
confidence: 97%
“…15,16 Nephrostomy tubes or other surgical intervention were required in a third of 1 series of 19 patients. 6 A literature review demonstrates that once lupus enteritis is found, there is a high likelihood of also demonstrating lupus cystitis, and vice versa. GI symptoms including vomiting, diarrhea, abdominal pain, ileus, malabsorption, colon ulcers, or ascites were described in 17 of 19 lupus cystitis patients in 1 review 6 and in 10 of 12 lupus patients with obstructive uropathy in 2 other case series.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The frequency is reported to occur in 0.5–1% of patients with SLE. Typical symptoms are suprapubic discomfort, dysuria, urgency, frequency, and nocturia [12]. The urine is sterile, ultrasound and CT scan show a markedly reduced bladder size with thickened bladder mucosa.…”
Section: Discussionmentioning
confidence: 99%